Sliding Mode Control for Position Tracking of Servo System with a Variable Loaded DC Motor - Durdu, Akif; Dursun, Emre Hasan (Elektronika ir Elektrotechnika, 2019)
In this paper, the real-time position control of servo system is carried out using sliding mode control (SMC) method based on variable structure control (VSC). As DC Motors are commonly used in many industrial applications and robotics, studies in this paper have are tested on a DC servo system, which is designed and produced by Quanser Inc. Three different types of sliding mode controllers are designed for position control of servo system and, later, performance comparison of DC Motor on Servo system is made. According to results obtained from real-time servo system, it is shown that SMC method is robust against to disturbing effects, variabilities, and uncertainties on the systems. Outstanding part of this paper is that designed controllers are implemented to servo system in real-time with a variable loaded DC Motor. Moreover, this study shows that this control structure can be performed as high performance in the real-time motor control applications.